Venous malformation presenting as Mauritia arabica-like bronchial wall thickness: a case report. Issue 11 (November 2022) - Lao, Miaochan; Gao, Ping; Liu, Yanhui; Yan, Lixu; Gao, Xinglin
Primary pulmonary venous malformation is rare and usually presents as single or multiple round masses or nodules. Here, we present the first report of a case of venous malformation presenting as Mauritia arabica -like bronchial wall thickness that was initially misdiagnosed as bronchiectasis. A Chinese man in his late 20s presented complaining of hemoptysis for 10 days. Computed tomography demonstrated bronchiectasis and M. arabica -like bronchial wall thickening in the left lower lobe. He was unresponsive to medical treatment for bronchiectasis and underwent thoracoscopic left lower lobectomy. Histopathological examination revealed venous malformation around the bronchial walls with no bronchiectasis. Venous malformation should be considered in the differential diagnosis of bronchiectasis, especially in patients with the following triad of signs: no response to antibiotics, M. arabica -like bronchial wall thickness, and normal accompanying arteries.